Mucocele in odontopediatric patient: a case report (Research, Society and Development, 2020)
The aim of this study is to describe a clinical case of mucocele in an odontopediatric patient. A 7-year-old female patient, leucodermic, sought care complaining of a discomfort in her lower lip when feeding. Clinical examination observed a circumscribed lesion, smooth surface, floating consistency to palpation, with color similar to that of the mucosa, approximately 10 mm in diameter, located on the left side of the lower lip. After anamnesis and clinical examination, it was possible to reach the probable diagnosis of mucocele. The treatment indicated was total surgical removal of the lesion. The surgical specimen was fixed in 10% formaldehyde and subsequently referred for histopathological analysis. The test result was compatible with mucocele type mucus extravasation, with no malignancy. It can be concluded that for the treatment of this type of lesion the complete surgical excision was effective, since after one year of treatment did not present recurrence, showing success in the approach of the case described.